2014
DOI: 10.1007/s10709-014-9811-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of the seed coat colour of Middle American and Andean bean seeds

Abstract: Seed coat colour of bean seeds is decisive for acceptance of a cultivar. The objectives of this research were to determine whether there is maternal effect for "L", a* and b* colour parameters in Middle American and Andean bean seeds; to obtain estimates of heritability and gain with selection for "L", a* and b* values; and select recombinants with the seed coat colour required by the market demand. Thus, controlled crossings were carried out between the Middle American lines CNFP 10104 and CHC 01-175, and bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 9 publications
4
21
1
1
Order By: Relevance
“…The L*, a*, and b* values presented discontinuous variation at the F 5:6 and F 5:7 generations ( Figure 1A, 1B, 1C, 1D, 1E, and 1F), indicating that few genes act in the manifestation of the seed coat color in common bean. Similarly, Possobom et al (2015) observed the formations of few phenotypic classes for the L*, a*, and b* values determined in recombinants of Mesoamerican and Andean common bean at the F 2 generation, which characterized a qualitative inheritance. The genetic control of the darkening of carioca beans was described as governed by two genes with recessive epistatic interaction (Silva et al, 2014;Erfatpour et al, 2018).…”
Section: Sources Of Variancementioning
confidence: 71%
See 4 more Smart Citations
“…The L*, a*, and b* values presented discontinuous variation at the F 5:6 and F 5:7 generations ( Figure 1A, 1B, 1C, 1D, 1E, and 1F), indicating that few genes act in the manifestation of the seed coat color in common bean. Similarly, Possobom et al (2015) observed the formations of few phenotypic classes for the L*, a*, and b* values determined in recombinants of Mesoamerican and Andean common bean at the F 2 generation, which characterized a qualitative inheritance. The genetic control of the darkening of carioca beans was described as governed by two genes with recessive epistatic interaction (Silva et al, 2014;Erfatpour et al, 2018).…”
Section: Sources Of Variancementioning
confidence: 71%
“…Nevertheless, for common bean no previous studies of heritability estimates for the a* and b* values in generation of high homozygosis were found in the literature. In segregating generation, Possobom et al (2015) verified high heritability for the L*, a*, and b* values in recombinants of Mesoamerican and Andean common bean. High heritability estimates are associated with the predominance of genetic variance.…”
Section: Genetic Variability and Genetic Parameters For Seed Coat Colmentioning
confidence: 73%
See 3 more Smart Citations